A predictive nomogram-based model for lower extremity compartment syndrome after trauma in the United States: a retrospective case-control study - Blake Callahan; Darwin Ang; Huazhi Liu (Journal of Trauma and Injury)
Purpose The aim of this study was to utilize the American College of Surgeons Trauma Quality Improvement Program (TQIP) database to identify risk factors associated with developing acute compartment syndrome (ACS) following lower extremity fractures. Specifically, a nomogram of variables was constructed in order to propose a risk calculator for ACS following lower extremity trauma. Methods A large retrospective case-control study was conducted using the TQIP database to identify risk factors associated with developing ACS following lower extremity fractures. Multivariable regression was used to identify significant risk factors and subsequently, these variables were implemented in a nomogram to develop a predictive model for developing ACS. Results Novel risk factors identified include venous thromboembolism prophylaxis type particularly unfractionated heparin (odds ratio [OR], 2.67; 95% confidence interval [CI], 2.33–3.05; P<0.001), blood product transfusions (blood per unit: OR 1.13 [95% CI, 1.09–1.18], P<0.001; platelets per unit: OR 1.16 [95% CI, 1.09–1.24], P<0.001; cryoprecipitate per unit: OR 1.13 [95% CI, 1.09–1.22], P=0.003). Conclusions This study provides evidence to believe that heparin use and blood product transfusions may be additional risk factors to evaluate when considering methods of risk stratification of lower extremity ACS. We propose a risk calculator using previously elucidated risk factors, as well as the risk factors demonstrated in this study. Our nomogram-based risk calculator is a tool that will aid in screening for high-risk patients for ACS and help in clinical decision-making.